Review article laser-induced hyperthermia on graphene oxide composites - Laura González-Rodríguez; Sara Pérez-Davila; Miriam López-Álvarez; Stefano Chiussi; Julia Serra; Pío González (Journal of Nanobiotechnology, 2023)
Abstract Background Hyperthermia-based therapies have shown great potential for clinical applications such as for the antitumor and antipathogenic activities. Within all strategies, the so-called photothermal therapy proposes to induce the hyperthermia by the remote laser radiation on a photothermal conversion agent, in contact with the target tissue. Methods This paper reviews the most relevant in vitro and in vivo studies focused on NIR laser-induced hyperthermia due to photoexcitation of graphene oxide (GO) and reduced graphene oxide (rGO). Relevant parameters such as the amount of GO/rGO, the influence of the laser wavelength and power density are considered. Moreover, the required temperature and exposure time for each antitumor/antipathogenic case are collected and unified in a thermal dose parameter: the CEM43. Results The calculated CEM43 thermal doses revealed a great variability for the same type of tumor/strain. In order to detect potential tendencies, the values were classified into four ranges, varying from CEM43 < 60 min to CEM43 ≥ 1 year. Thus, a preference for moderate thermal doses of CEM43 < 1 year was detected in antitumor activity, with temperatures ≤ 50 °C and exposure time ≤ 15 min. In case of the antipathogenic studies, the most used thermal dose was higher, CEM43 ≥ 1 year, with ablative hyperthermia (> 60ºC). Conclusions The ability of GO/rGO as effective photothermal conversion agents to promote a controlled hyperthermia is proven. The variability found for the CEM43 thermal doses on the reviewed studies reveals the potentiality to evaluate, for each application, the use of lower temperatures, by modulating time and/or repetitions in the doses.